Photogrammetry for Augmented Reality, A Low-Cost Method Applied to 3D Modeling in Secondary Schools - Quintero-Madroñero, Jairo-Hernando; Baldiris-Navarro, Silvia-Margarita; Cerón-Cháves, Jhoni-Ricardo; Burgos, Daniel; Muñoz-Erazo, Yerson; Jurado-Ortega, Luis-Carlos; Meneses-Díaz, Edinson-José (Revista Facultad de Ingeniería, 2021)
Augmented Reality (AR) is an emerging technology known for supporting the educational process at different levels, and that is complemented and enhanced nowadays with the increased use of mobile devices. In this sense, some barriers have been identified both in practice and in the literature that minimize the development of mobile applications with this technology, mainly at the levels of elementary school and high school; one of them is 3D modeling, which may take longer and, at the same time, become a challenging process at that educational level. To address this concern, we have designed a method aimed at users with low digital knowledge, and it is complemented with a series of recommendations that allow the use of the photogrammetry technique to generate three-dimensional models in an easy, affordable, and low-cost way. To validate the method, a co-creation team of teachers and tenth-grade students was created and given the task of building 3D objects for three mobile applications developed around different subjects. Subsequently, the evaluation was carried out from two perspectives: a) the co-creation group analyzed the quality of each of the objects generated, b) the applications were evaluated by a group of experts on the subject, taking into account their performance according to usability heuristics. It was a case study where the students also participated in the evaluation of an application. When following the proposed method, the quality and results of the applications evidenced a promising future for developments in the educational field, even for other levels of study.